Mengoptimalkan pemahaman konsep matematis dan motivasi belajar: Eksplorasi think pair square pada kelas VII MTs Nur Et-Taqwa Cikande - Purwaningsih, Zenny; Nasrullah, Anton; Hidayat, Amat; Hidayanti, Nur; Mahuda, Isnaini; Caesarani, Sarah (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2025)
Problems experienced by students include low understanding of mathematical concepts and lack of learning motivation. This study aims to examine the extent to which the Think Pair Square (TPS) cooperative learning model can be a solution to improve both aspects. This study design is a quasi-experimental study with two groups: an experimental group and a control group. Data were collected through a mathematical concept understanding test and a learning motivation questionnaire. Data analysis was carried out using a paired t-test, N-Gain calculation, and descriptive analysis using a Likert scale. The results of the study showed a significant increase in the understanding of mathematical concepts and learning motivation of students in the experimental group. The application of collaborative learning strategies has been proven to help students build a deeper understanding of concepts and increase their engagement in the mathematics learning process.